A formação de professores do ensino liceal. A Escola Normal Superior da Universidade de Coimbra (1911-1930) - António Gomes Ferreira; Luís Mota (Universidade do Minho, 2013)
Our analysis focuses on the model of teacher training from Escolas Normais Superiores, particularly concerning the school belonging to the University of Coimbra. Inspired by the École Normale Supérieure in Paris, those institutions were marked by the pedagogy of the New School Movement, carrying innovative proposals. A key part of a wider educational project initiated by Republicans after October 1910, founded on the belief of regenerating homeland by education, the creation of a new citizen and the building of the Republican nation, these institutions constituted the first attempt to train teachers on all levels of education, except the general primary education. On an ideal and theoretical perspective, the legislation meant a significant milestone in our history of education (Gomes, 1990). However, the context and conditions, including materials, prevented the school from becoming the desired model.